IDIOM BAHASA INGGRIS BERUNSUR BAGIAN TUBUH MANUSIA DAN PADANANNYA DALAM BAHASA INDONESIA - , HERLITA SUSANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Subject discusses about English idiom in accordance with Indonesian Idiom. The aim of this research is to describe English Idioms form which use part of human body uses